The Molecular Biology Capstone Assessment: A Concept Assessment for Upper-Division Molecular Biology Students - Couch, Brian A. (CBE Life Sci Educ, 2015)
Measuring students’ conceptual understandings has become increasingly important to biology faculty members involved in evaluating and improving departmental programs. We developed the Molecular Biology Capstone Assessment (MBCA) to gauge comprehension of fundamental concepts in molecular and cell biology and the ability to apply these concepts in novel scenarios. Targeted at graduating students, the MBCA consists of 18 multiple-true/false (T/F) questions. Each question consists of a narrative stem followed by four T/F statements, which allows a more detailed assessment of student understanding than the traditional multiple-choice format. Questions were iteratively developed with extensive faculty and student feedback, including validation through faculty reviews and response validation through student interviews. The final assessment was taken online by 504 students in upper-division courses at seven institutions. Data from this administration indicate that the MBCA has acceptable levels of internal reliability (α = 0.80) and test–retest stability (r = 0.93). Students achieved a wide range of scores with a 67% overall average. Performance results suggest that students have an incomplete understanding of many molecular biology concepts and continue to hold incorrect conceptions previously documented among introductory-level students. By pinpointing areas of conceptual difficulty, the MBCA can provide faculty members with guidance for improving undergraduate biology programs.